2018
DOI: 10.1002/elan.201800109
|View full text |Cite
|
Sign up to set email alerts
|

J. Heyrovský's Oscillographic Polarography. Roots of Present Chronopotentiometric Analysis of Biomacromolecules

Abstract: In 1941 J. Heyrovský invented Oscillographic Polarography (OP) with controlled alternating current (a.c.). The method was developed during the World War and the first commercially available instruments for OP were produced in Czechoslovakia at the beginning of the 1950’s. Such instruments offered derivative and cyclic OP curves allowing simple analysis of various compounds and stimulated the publication of hundreds of papers. Thanks to OP, electrochemical analysis of DNA started already in 1958. According to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 150 publications
(168 reference statements)
0
18
0
Order By: Relevance
“…The proposed MD approach can be applied in the interpretation of experimental data on the interfacial behavior of peptides at Hg‐surfaces. The main focus of attention has to be on the catalytic hydrogen evolution reaction (CHER) of peptides, where mercury electrodes play a unique role in the study of structural changes and biologically relevant interactions of the peptides containing proton‐donating amino acid residues . The first chronopotentiometric stripping observation of a CHER of peptides at a Hg‐electrode was performed 20 years ago by E. Paleček and co‐workers .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed MD approach can be applied in the interpretation of experimental data on the interfacial behavior of peptides at Hg‐surfaces. The main focus of attention has to be on the catalytic hydrogen evolution reaction (CHER) of peptides, where mercury electrodes play a unique role in the study of structural changes and biologically relevant interactions of the peptides containing proton‐donating amino acid residues . The first chronopotentiometric stripping observation of a CHER of peptides at a Hg‐electrode was performed 20 years ago by E. Paleček and co‐workers .…”
Section: Discussionmentioning
confidence: 99%
“…In 1998 E. Paleček and co‐workers found that CHER of peptides can be observed by chronopotentiometric stripping (CPS) producing a typical analytical output, the so‐called peak H . Peak H not only enables the highly sensitive label‐free and reagentless detection of biomolecules, but it is also highly sensitive to changes in their structures as well as to their intermolecular interactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this accumulated knowledge it is not surprising that the Cys‐p53 aptamer exhibits a good catalytic activity towards the hydrogen evolution at the mercury electrode. Indeed, around the physiological pH, the amino acid residues which are the most active for the catalytic hydrogen evolution reaction are Cys, Lys, and Arg , the aptamer containing the former two. In addition, the peptide must be present at the electrode at the potential (and at the moment) at which the catalysis takes place.…”
Section: Resultsmentioning
confidence: 99%
“…With his coworkers, he showed that at mercury (and amalgam) electrodes, all proteins exhibit a catalytic activity towards the hydrogen evolution reaction, giving rise in constant current chronopotentiometry to very intense peaks of great analytical significance owing to their high sensitivity to numerous parameters . This typical chronopotentiometric peak was coined as “Peak H” for H eyrovsky, H ydrogen evolution and H igh sensitivity , and various authoritative reviews on its analytical values are available . Herein, it is demonstrated that the peak H is not only useful for analytical purposes, but also for interfacial characterisations of relevant model systems.…”
Section: Introductionmentioning
confidence: 99%